2021
DOI: 10.1016/j.ebiom.2021.103439
|View full text |Cite
|
Sign up to set email alerts
|

50-gene risk profiles in peripheral blood predict COVID-19 outcomes: A retrospective, multicenter cohort study

Abstract: Background COVID-19 has been associated with Interstitial Lung Disease features. The immune transcriptomic overlap between Idiopathic Pulmonary Fibrosis (IPF) and COVID-19 has not been investigated. Methods we analyzed blood transcript levels of 50 genes known to predict IPF mortality in three COVID-19 and two IPF cohorts. The Scoring Algorithm of Molecular Subphenotypes (SAMS) was applied to distinguish high versus low-risk profiles in all cohorts. SAMS cutoffs derived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 31 publications
3
15
0
Order By: Relevance
“…COVID-19 gene expression prognosis studies are limited (33,34). Scoring algorithm of molecular subphenotypes (SAMS) have been used to identify 50-gene risk profiles for COVID-19 which discriminate between mild and severe disease (33) The importance of genes in a classification of ICU admission with Random Forest.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…COVID-19 gene expression prognosis studies are limited (33,34). Scoring algorithm of molecular subphenotypes (SAMS) have been used to identify 50-gene risk profiles for COVID-19 which discriminate between mild and severe disease (33) The importance of genes in a classification of ICU admission with Random Forest.…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 gene expression prognosis studies are limited (33,34). Scoring algorithm of molecular subphenotypes (SAMS) have been used to identify 50-gene risk profiles for COVID-19 which discriminate between mild and severe disease (33) The importance of genes in a classification of ICU admission with Random Forest. The higher the value of importance of the variable (mean decrease gini score), the higher the importance of the gene(s) in the model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When COVID-19 first came out in 2019, people found there was a strong link between IPF and COVID-19 ( Uzel et al, 2020 ; Zhang C. et al, 2021 ). As a study showed that fifty-gene profiles in peripheral blood can predict the outcomes of IPF and COVID-19 patients ( Juan Guardela et al, 2021 ). We supposed that interaction between IPF and COVID-19 may be through some key genes, so the present study was intended to explore some hub genes both involved in IPF and COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…It results in inflammation, fibrosis, lung damage, and edema. Hyper-inflammation by SARS-CoV-2 induces fibroblast activation, increased extracellular matrix, and collagen deposition leading to PF, similar to the features of interstitial lung disease (ILD) [ 13 , 14 ]. It is known that risk factors for PF include old age, comorbidities, ICU admission, and MV [ 7 , 13 ].…”
Section: Introductionmentioning
confidence: 99%